PENGARUH KEPEMIMPINAN, KOMUNIKASI, MOTIVASI DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI - Ely Kusmiran, 08.3502.0562; Wanuri, Wanuri (Students Journal of Economic and Management, 2012)
This study is to test the influence of leadership, communication, motivation, and promotion on employee performance. One attempt to improve quality of human resources is a good leadership, communication within the organization is good, high employee motivation and promotions based on employee perfomance. Perfomance assessment is an important factor in determining salary increase and employee career development. In this study, researchers used a validity test to measure the level of test validity and reliability of an instrument to measure the stability of a measuring instrument in measuring a symptom. After testing the validity and reliability, then the next step researchers formulate regression equations. As formulated the regression analysis that is oftenused to predict how big the effect of independent variables on the dependent variable. The result is a variable leadership, communication, motivation, and promotion has a positive value or improve employee performance. This means that the higher the influence of leadership, communication, motivation, and promotion the higher employee performance. This studies have limitations, namely a short sampling period and do not consider other key variables that can affect the perfomance of the employee. Therefore, further research is suggested to consider the other main variables and the time of the study need to be even longer so that it can be generalized. Key words leadership, communication, motivation, promotion on employee, performance